Effect of the Phytase Inclusion in Broiler Breeder Diets on Fecal and Egg Characteristics - Nusairat, Basheer; Ramos, Mireille Arguelles; Brake , John (International Journal of Poultry Science, 2017)
Objective: A study was conducted to determine the effect of phytase inclusion in broiler breeder diets on fecal and egg characteristics of individually caged females. Materials and Methods: A total of 184 female broiler breeders were fed growing and laying diets containing 0.7% or 2.7% calcium (Ca) and 0.35% or 0.12% available phosphorus (AvP), respectively, with one of four graded levels of phytase 0 (Control), 300, 600 and 1200 FTU kg–1 with 46 replicate cages/treatment at photostimulation. Results: Feeding 1200 FTU kg–1 of phytase produced greater fecal liquid portion at 31 week (p<0.001) and 38 week (p<0.01) while fecal phosphorus (P) was increased (p<0.01) at 38 week in birds that had consumed either 600 or 1200 FTU kg–1 of phytase. There was no significant effect of phytase on egg characteristics or egg production. Conclusion: When formulating broiler breeder diets with phytase, attention should be made to the quantity of enzyme used to avoid increased liquid feces.